Test the Cardioprotective Effectiveness of Turmeric Ethanol Extract (Curcuma Longa) in Doxorubicin-In-Rat Wistar (Rattus Norvegicus) Doxorubicin-Induced Males - Wang Xiqin; Florenly Florenly; Liena Liena; Johannes Bastira (Budapest International Research and Critics University, 2021)
Cardiotoxicity is mostly due to the use of chemotherapy drugs, with the class of anthracyclines drugs being 86.8. One of the most commonly used anthracyclines is doxorubicin. Turmeric with the scientific name Curcuma longa linn is one of the medicinal plants, the main compound is curcumin is considered able to reduce the risk of heart attack. The goal of this study tested the cardioprotective effectiveness of turmeric ethanol extract (curcuma longa linn.) in doxorubicin-induced male wistar (rattus norvegicus) mice. This type of research is experimental, in the Pharmacology Laboratory of the Faculty of Pharmacy, University of North Sumatra, and November 2020. Animals experimented on male wistar rats (Rattus norvegicus) weighing 150 - 200 grams. Data analysis, if (P > 0.05), continued with One Way ANOVA, but if (P <.05) followed by the Tukey HSD Post Hoc test to see real differences between treatments. If the distributed data is abnormal then the Kruskal-Wallis test results are used. Statistical test results, serum levels of CK–MB in the normal group have significant differences (p<0.05) with the negative control treatment group and the treatment group I, but do not have a significant difference (p>0.05) with the positive control group, treatment group II and the treatment group III. Concluding that turmeric ethanol extract has the ability to lower levels of biomarkers of heart damage namely CK-MB and LDH induced with doxorubicin, gradually increasing doses of turmeric ethanol extract can reduce the incidence of heart cell damage, which is most effective at doses of EEK 500 mg / kg BB. Turmeric ethanol extract has cardioprotective effects induced with doxorubicin. Administration of turmeric ethanol extract can repair heart organ tissue induced with doxorubicin based on histological picture of the heart. It is hoped that researchers will be able to conduct research on the toxic effects of giving turmeric ethanol extract to the hearts of mice conducted subchronically.